APPLICABILITY OF ADOPTING MORPHOLOGICAL PATTERNS IN PEDIATRIC ANEMIAS AS ETIOLOGICAL INDICATORS - A L, Hemalatha; S N, Shobha; K P, Ashok; B M, Sarvesh; D, Nanjundswamy; Sahni, Swati; C R, Raghuveer (International Journal of Clinical and Biomedical Research, 2015)
Background: Pediatric anemia is a global phenomenon. The magnitude of this problem gets exaggerated in developing countries like India wherein majority of the population are vulnerable since they live in rural areas and come under low socio-economic status. Though pediatric anemias can be diagnosed by simple blood tests like complete hemogram and peripheral smear examination, the evaluation of underlying etiological factor to initiate appropriate therapy involves expensive work up which may not be affordable in a rural setup. This need-based study of pediatric anemia was conducted to determine the morphological patterns of anemia by simple baseline investigations and to detect the related etiologic factor. Methodology: The probable etiological factors contributing to the anemias were diagnosed by determining the morphological patterns using simple baseline investigations like complete hemogram and peripheral blood examination and treated accordingly. Conclusion: The etiology of microcytic hypochromic anemia was found out to be iron deficiency as confirmed by serum iron profile studies. Presence of dimorphic anemia suggested combined nutritional deficiency of Iron, vitamin B12 deficiency or folate. Hemolytic anemias detected by routine hematological investigations were confirmed by serum electrophoresis. Morphological examination of red blood cells on peripheral smear examination is thus an effective, simple and cost effective method to determine the etiology of various types of anemia. KEYWORDS: Peripheral blood smear examination; Baseline investigation; Patient management.